Pitiríase rósea Pityriasis rosea - Sandra Maria Bitencourt Miranda; Délio Delmaestro; Paulo Bittencourt de Miranda; Absalom Lima Filgueira; Luciane Faria de Souza Pontes (Sociedade Brasileira de Dermatologia, 2008)
Pitiríase rósea é doença inflamatória aguda da pele, que regride espontaneamente, normalmente sem deixar seqüelas, em período que varia de quatro a oito semanas. Clinicamente é caracterizada pelo aparecimento de típicas lesões eritêmato-pápulo-escamosas. Atinge todas as idades, embora seja mais comumente observada entre 10 e 35 anos. Apesar de exaustivas pesquisas, sua etiologia ainda permanece desconhecida. São discutidos alguns aspectos epidemiológicos, anatomoclínicos, diagnósticos diferenciais, doenças associadas, com ênfase no tratamento e etiologia da doença. Pityriasis rosea is a skin disease characterized by acute inflammation that fades away spontaneously without scar tissue formation for an average period of 4 to 8 weeks. Clinically, it is characterized by the occurrence of typical erythematous papulosquamous lesions distributed mainly over the trunk and extremities. It affects people of all ages, but is more often observed in the age range of 10 to 35 years. Even though it is extensively studied, its etiology remains unknown. In this study, the authors analyze some epidemiologic aspects, differential diagnosis, related diseases, and give special attention to treatment and possible etiology.